Kontribusi Ibu Rumah Tangga Terhadap Pendapatan Ekonomi Keluarga Dalam Usaha Kerajinan Sarung Tenun Di Kecamatan Samarinda Seberang (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2020)
Yulius Bakkula, 2019. Contribution of Housewife to Family Economic Income in weaving sarong Business in Samarinda Seberang District. ( under the guidance of Mr. Dr.H. Adi Wijaya, M.Si. and Mr. Andriawan Kustiawan, SE.,M.Si                        This study aims to determine what contributions are made by housewives who work as weaving sarung craftsmen in the domestic and domestic sektors in increasing the family’s economic income in the weaving village of Samarinda sub-district, Samarinda. This research was carried out in the district of Samarind opposite, precisely in the village of weaving. With many sampels of 10% out of a total people, there were 10 sampels that were studied.                        This research method uses qualitative research. Researchers took data by interview, observation, and documentation techniques. The results of this study indicate that the contribution of housewives in increasing household income can be seen from the income received by housewives.  With the operation of the wife, the role automatically becomes double, that is to become a housewife who takes care of the house and a housewife who works.